Embryonic stem cells: the disagreement debate and embryonic stem cell research in Israel - Simonstein, F. (Journal of medical ethics, 2008)
While some people claim that the present disagreement over embryonic stem (ES) cell research cannot be resolved, others argue that developing transparency and trust are key elements that could resolve the existing disagreements over such research. This paper reveals that transparency is not necessarily a requirement for advancing ES cell research, since in Israel, for instance, there is (almost) no transparency, and research nevertheless flourishes. Moreover, trust is not independent of cultural values and religious beliefs. Because of these beliefs, the environment in Israel for ES cell research has been pragmatic and liberal. The Israeli case illustrates the key role that culture and religion can play in biomedical research; it also suggests that as far as cultural values or religious beliefs of people in Western countries strongly oppose research on embryonic tissue, it would be very difficult, if not impossible, to overcome the disagreements.